Genetic Relationship Between Colony Colour and Polyoxin Resistance in Cochliobolus heterostrophus - Abdul Gafur (Universitas Gadjah Mada, 2001)
Three reddish, polyoxin-resistant mutant strains of Cochliobolus heterostrophus (Drechsler) Drechsler (MIC > 1600 μg/ml), i.e. NA1, PRE058, and TE2, were isolated after ethyl methanesulphonate (EMS) mutagenesis. The resistant mutants were crossed to each other and to the greeny, sensitive wild type strain to investigate genetic relationship between colony colour and polyoxin resistance traits in the fungus. Progeny analyses showed that colony colour and polyoxin resistance in the three resistant mutants were conferred by monogenic genes. No linkage was detected in the present study between the genes controlling colony colour and polyoxin resistance traits in the fungus.